Palaeoarchaean felsic magmatism: A melt inclusion study of 3.45Ga old rhyolites from the Barberton Greenstone Belt, South Africa - Agangi, Andrea; Hofmann, A.; Kamenetsky, V.; Vroon, P. (Elsevier, 2015)
© 2015 Elsevier B.V. The 3.45 Ga old felsic volcanic rocks from the Barberton Greenstone Belt of southern Africa include a submarine succession of felsic lavas and volcaniclastic rocks and shallow subvolcanic intrusions. Sea floor alteration strongly affected rock compositions shortly after emplacement, making comparisons with coeval intrusions challenging. We analysed well-preserved quartz-hosted melt inclusions from the felsic rocks, which offers a unique opportunity to gain insight into pre-alteration melt compositions. Melt inclusion compositions are then compared with whole-rock analyses to evaluate the significance of the volcanic complex in the context of Archaean felsic magmatism in the Barberton Greenstone Belt. Whole-rock immobile trace element concentrations, including high-field strength and rare earth elements, indicate strong similarities with coeval tonalite-trondhjemite-granodiorite intrusions. These same geochemical characteristics distinguish these rocks from other Archaean felsic rocks in the Barberton Greenstone Belt (e.g. the 3.54Ga Theespruit Formation), which have characteristically higher Th, Nb and REE. Low CaO (=1wt.%) and relatively high Nb and Th (mostly =9 and =13ppm, respectively) in comparison with least altered whole-rock samples, and the presence of negative Eu anomalies are consistent with the melt inclusions being relatively evolved, rather than representing primitive compositions. Melt inclusion analyses suggest the presence of two melts with varying K2O/Na2O. Melt inclusions from extrusive samples, which contain remnants of K-feldspar phenocrysts, have K2O/Na2O>1 by weight, whereas subvolcanic intrusions, which contain Na-rich plagioclase, have K2O/Na2O<1. Moderately high Cl contents (Cl=0.7wt.%) of melt inclusions may record interaction of the melting protolith with sea water prior to melting. We speculate that the varying K2O/Na2O in the felsic volcanic rocks was due to melting of a greenstone succession heterogeneously affected by sea floor alteration.